Direct atom probe tomography observations of concentration fluctuations in Fe–Cr solid solution. (15th March 2015) - Zhou, Jing; Odqvist, Joakim; Ågren, John; Ruban, Andrei; Thuvander, Mattias; Xiong, Wei; Olson, Gregory B.; Hedström, Peter
Abstract : The local concentration of atoms in an Fe–46.5 at.% Cr alloy, solution treated at four different temperatures above the miscibility gap, has been investigated using atom probe tomography. It is experimentally found that Cr atoms cluster in the solid solution and that the clustering tendency decreases with increasing temperature above the miscibility gap. These findings are corroborated by Monte Carlo simulations of the atomic short-range order, which show that clustering markedly decrease with increasing temperature from 800 to 1200 °C.